Efects of acute sodium bicarbonate supplementation on repeate sprint ability in female football players - Barata, Cláudia Patrícia Fernandes (2022)
This study sought to investigate the effects of acute sodium bicarbonate (SB) supplementation on repeated sprint ability in female football players. Eleven athletes completed a double blind randomized crossover controlled trial with 2 repeated sprint sessions (SB or placebo, PL) performed in a cycle ergometer, consisting of 3 x 6 maximal 6-s sprints performed every 30 s with 5-min recovery between sets. The first take (0.2 g/kg) of the supplement was ingested 120 minutes before the exercise protocol and the second take (0.1 g/kg) 60 minutes before. Sodium bicarbonate allowed a higher blood lactate accumulation (Max - SB: 14.0±4.32 vs PL: 10.9±3.55, p=0.010), induced a greater elimination of CO2 (p=0.038) through ventilation and showed a tendency to provide a larger muscle oxygenation. These metabolic effects did not traduce into major benefits in terms of power output and total work performed in the task other than preventing a decline in mean power output in the second set. Sodium bicarbonate also favoured neuromuscular performance, inducing a smaller decrement on jump height in a countermovement jump (SB: -0.8% vs PL: -7.4%). This research suggests that female football players may benefit from sodium bicarbonate supplementation to support the high physiological demands of the game.